2018
DOI: 10.1115/1.4041465
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of Optimized Blade Tip Shapes—Part I: Turbine Rainbow Rotor Testing and Numerical Methods

Abstract: Blade tip design and tip leakage flows are crucial aspects for the development of modern aero-engines. The inevitable clearance between stationary and rotating parts in turbine stages generates high-enthalpy unsteady leakage flows that strongly reduce the engine efficiency and can cause thermally induced blade failures. An improved understanding of the tip flow physics is essential to refine the current design strategies and achieve increased turbine aerothermal performance. However, while past studies have ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…At the outlet, the Reynolds based on the rotor axial chord was 2.76 × 10 5 , reached at high-subsonic conditions (relative Mach number of 0.78). A more detailed characterization of the experimental campaign boundary conditions was provided by the authors in [16].…”
Section: Operating Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the outlet, the Reynolds based on the rotor axial chord was 2.76 × 10 5 , reached at high-subsonic conditions (relative Mach number of 0.78). A more detailed characterization of the experimental campaign boundary conditions was provided by the authors in [16].…”
Section: Operating Conditionsmentioning
confidence: 99%
“…The instantaneous rotor angular position was monitored by optical shaft encoders with an accuracy of ±0.25% of the rotor pitch at a rotational speed of 5900 rpm. Five blade passages per revolution were therefore considered for each single tip profile, leading to a total of 23 × 5 = 115 blade periods per test [16].…”
Section: Signal Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Then, more and more researchers focused on the geometric optimization of the squealer tip, such as the number and layout of rims, [12][13][14] cutback configurations, 15,16 and the width and depth of rims. 17,18 The researchers from the von Karman Institute for Fluid Dynamics (VKI) [19][20][21] tried to optimize the squealer-like tip geometry by using the differential evolution algorithm and finally obtained the double-cavity tip configuration with great aerodynamic and thermal performance. Prakash et al 22 found that the inclined PSSR could increase the blocking area caused by the flow separation on the top of the rim, controlling the TLF.…”
Section: Introductionmentioning
confidence: 99%
“…With this setup, they achieved blade-to-blade variations in the tip radius below ±0.1 mm. The same setup was used by (Cernat et al, 2018) for the combined aerothermal testing of tip designs, where high-frequency pressure and temperature instrumentation at the rotor casing was used. The time average pressure and heat transfer at the casing was found to vary significantly with blade tip geometry, as a function of blade passage and tip gap position.…”
Section: Introductionmentioning
confidence: 99%